Talent management practices and the performance of firms: Evidence from Polish SMEs - Aleksy Pocztowski; Urban Pauli (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: This article aims to identify and explore a potential relationship between talent management (TM) practices and performance in small and medium-sized enterprises (SMEs). Despite the growing number of publications on talent management, scholars rarely investigate such a link in this type of enterprise. Research Design & Methods: We collected data from 200 randomly selected Polish SMEs. We interviewed respondents about the characteristics of TM practices they apply and the performance they achieve. The data revealed three clusters of approaches to TM (acquisition, retention, and complex) and two frequencies in running talent management activities (systematic and occasional). These verified a potential link with HR-related, organisational, and business performance outcomes. Findings: Analyses revealed a statistically significant relationship between TM practices and most HR-related outcomes, some organizational outcomes, and almost no business performance outcomes. Moreover, we proved relationships between approaches to talent management and some performance indicators. Implications & Recommendations: Small and medium-sized enterprises benefit from using a systematic approach to TM in the form of a positive impact on particular performance areas referring to business outcomes and brand recognition. The TM practices SMEs apply help overcome challenges they face. Thus, we advise defining the main goal of TM should before undertaking particular actions. Contribution & Value Added: This article contributes to the body of knowledge on TM in SMEs and explores the relationship between TM practices and performance. Part of the examined relationships between indicators of TM and those describing performance was confirmed as statistically significant.
Keywords: M12; M51; M54; 330; talent management; performance; TM outcomes; HRM in SMEs; SMEs